Analisis Literasi Keuangan Syariah pada Ulama Muhammadiyah di Kabupaten Cirebon - Muhamad Faizal Reza; Yanuar Isyanto; Karlina (Rayah Al-Islam, 2025)
This study aims to analyze the level of Islamic financial literacy among Muhammadiyah scholars in Cirebon Regency. Islamic financial literacy plays a strategic role in promoting the use of financial products and services that comply with Sharia principles. This research employs a qualitative descriptive approach using in-depth interviews with several Muhammadiyah scholars who possess religious authority and social influence. The collected data were analyzed descriptively through the stages of data reduction, presentation, and conclusion drawing, accompanied by source triangulation to ensure validity. The findings indicate that most Muhammadiyah scholars possess a solid basic understanding of Islamic financial principles; however, their comprehension of Sharia contracts and contemporary financial instruments remains limited. Factors such as educational background, experience, access to information, and engagement in Sharia-based economic activities significantly influence their level of literacy. These results underscore the necessity of more structured and continuous Islamic financial education and mentoring programs for scholars so that they can play a more effective role as agents of Islamic economic literacy within society.